The Effect Of Competence and Independence to Work Effectiveness Of Auditor - Ismet Sulila (Publik : (Jurnal Ilmu Administrasi), 2020)
The research objective was to find out the influence of competence and independence on the work effectiveness of auditor at Regional Inspectorate of Gorontalo Province either partially or simultaneously. The approach used in this research was quantitative. The research method used expost facto. The technique of data analysis used multiple regression. The research finding showed that (1) competence of auditor had a positive and significant influence on the work effectiveness of auditor at Regional Inspectorate of Gorontalo Province by the determinant value of 23,50%. The meaning of the positive coefficient indicated that the higher the competence of auditor, the more effective work result of auditor at Regional Inspectorate of Gorontalo Province. (2) Independence of auditor had a positive and significant influence on the work effectiveness of auditor at Regional Inspectorate of Gorontalo Province by determinant value of 56,60%. The meaning of positive coefficient indicated that the more independent of auditor in doing inspection and functional supervision function, the more optimum work effectiveness of auditor at Regional Inspectorate of Gorontalo Province. (3) The competence and independence of auditor, simultaneously, had a significant influence on the work effectiveness of auditor at Regional Inspectorate of Gorontalo Province by determinant value of 61,70%.